Are China’s service exports accurately measured? Implications of an alternative measurement approach - Dong, Hang Hang; Yong, Chen Chen (Institute of China Studies, 2018)
As economic development advances, a country’s service sector grows. With globalization, this growth is often accompanied by the growth of trade in services. China is a good example. After three decades of spectacular economic advance, its service trade is now one of the world’s largest, but so is its service trade deficit. How did this come about, given China’s competitive strength in the export of goods? Second, is this deficit a statistical anomaly, i.e. with China participating in global supply chains, how well do gross exports reflect the true value of China’s service exports? Third, what is the real competitiveness of China’s service exports? This study examines these questions by first reviewing the structure and trends in China’s service trade using official statistics. It then re-estimates these exports using the “forward linkage value-added method” to compare with gross exports. The third question is addressed by calculating revealed comparative advantage (RCA) indexes based on gross as well as value-added service exports. Using 2000-2014 data, the results show that no matter which method is applied, China’s service exports have weak comparative advantage but rising RCAs show China’s competitive situation improving. Also, gross export values overestimate the RCA compared to value-added values. A number of policy implications arise from these findings.